Kompilasi Hukum Islam dalam Pandangan Ulama Madzhab dan Pengaruhnya dalam Berumah Tangga dalam Taklik Talak - Sofyan Yusuf; Muhtadi (Arsy : Jurnal Studi Islam, 2021)
Article 1 letter e of Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law (KHI) states that taklik talak is an agreement that is pronounced by the prospective groom after the marriage contract which is included in the marriage certificate in the form of a promise of divorce which is hung on certain circumstances that come. The Marriage Agreement in the Compilation of Islamic Law (KHI) is contained in CHAPTER VII which regulates taklik talak as contained in Article 45 and Article 46. In Sunnah Fiqh that marriage agreement called taklik talak there are two kinds of talik talak qasami and taklik divorce syarti. Taklik qasami talak is taklik which is meant as a promise. Meanwhile, taklik talak syarti is taklik which is intended to impose divorce if the conditions for taklik have been fulfilled. Taklik talak also has an important role in domestic life. This study uses a qualitative descriptive method. collection of data and legal materials, both primary, secondary and tertiary, cases collected through observation, interviews, and studies of legal documents, while the analysis technique was carried out qualitatively. The results showed that the marriage agreement related to taklik talak is regulated in articles 45 and 46 of the Compilation of Islamic Law (KHI). The contents of the taklik talak agreement have been determined by the Minister of Religion and published by the Ministry of Religion, because the people who make this taklik talak agreement are only Muslims, then the contents of the taklik talak agreement must not conflict with Islamic law. Jumhur Ulama is of the opinion that there are two forms of taklik that are associated with talak/promise. Meanwhile, Ibn Hazm and Ibn Oayyim al-Jauziyah are of the opinion that taklik which contains the intent of the oath (qasami) does not result in the fall of divorce, but is obliged to pay the kifarat of the oath and ta'lik which contains conditions intended to impose divorce when something happens. required, then the divorce falls. The existence of taklik talak which has been supported by clear legal force in the Compilation of Islamic Law, and supported by the opinion of Ulama - ulama with strong arguments and their influence on the existence of women adds to the importance of taklik talak in domestic life. And the position of women will be more meaningful because it will avoid the husband's arbitrariness